PRODUKSI PUPUK ORGANIK CAIR CROCOBER PLUS KEGIATAN MBKM BAGI MAHASISWA MAGANG - Jamilah Jamilah; Milda Ernita; Yulia Rahmawati. Z (Universitas Mataram, 2023)
Fertilizer is vital for farmers to cultivate plants. The problem with fertilizer is that high prices make farmers' purchasing power low, therefore agricultural results do not meet expectations. Procuring organic fertilizer is easier and cheaper, because organic materials are not only cheap but also abundant in Indonesia. The aim of the activity to provide education and training to students in producing POC Crocober Plus and its application in onion plants. Increasing the ability of MBKM students to be able to develop an entrepreneurial spirit. Socialization and direction of activities starting from preparation until the end of the activity. Practice making POC Crocober Plus fertilizer. Application of POC Crocober Plus in the field for onion plants. The results of the activities carried out were the implementation of internship activities in the MBKM program totaling 3 credits which were carried out in the Agricultural Faculty workshop room and in the field in Alahan Panjang, Solok Regency, specifically for horticultural crops. In this activity students are trained to produce commercial POC and its application to onion plants. The importance of socializing the production of POC Crocober Plus is to increase student competency in producing fertilizer in an effort to replace some of the need for artificial fertilizer. Intern students need to know the correct techniques for making POC to produce premium quality.